The Use of Flipped Learning Strategy in Teaching English Vocabulary at Elementary School - Imam nur Aziz; Ita Sari Ziyadah Rohmah (JEET, Journal of English Education and Technology, 2022)
This study aims to know the effect of Flipped learning strategy on students' vocabulary achievement at pesantren—pre-experimental one-group pretest-posttest design used to determine the dependent variable's accuracy. Sixty elementary students at Pesantren Mambaush Sholihin Gresik assessed a significant influence on vocabulary achievement. The finding shows that data using a paired-sample t-test was 12,817 at the considerable level of 0,05 and the degree of freedom 29. The flipped learning method was significant and affected improving students' vocabulary in primary school. The learning impact will be considerably decreased if the group's division of labour is ambiguous and students do not participate actively in the group. Because of this, future implementations of flipped classes should be revised.